Combined ability of salicylic acid and spermidine to mitigate the individual and interactive effects of drought and chromium stress in maize (Zea mays L.) - Naz, Rabia (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.